The Epistemology of “Contemporary Art” Noumenon (Global Journal of Science Frontier Research, 2020)
“Contemporary art” is universal, but in international commonality, Chinese contemporary art has its specific problems that it faces: this includes scientific falsification and critique of artistic conspiracy and deception, highlighting the contemporary nature of contemporary art’s cognitive function, and connecting relationship with theory and practice, history and logic between contemporary art and artistic phenomenology, such as “world 2,” “practice-spirit” and behavior, installation, etc., thus welcoming the world identity of “cognitive experience” and “spiritual practice.” From the above three parts, the article identifies, “contemporary art” is a view of problem consciousness, concept, and human beings’ independent personality and dignity. On the historical approach and value orientation, she is not only a historical uplift to the function of art cognition but also a historic approach and representation of the era of “cultural experience” and “civilized practice.”
Keywords: contemporary art; conspiracy theory; world 2; cognitive experience; spiritual practice; the way of grasping the world